Impact of Climate on Agricultural Production in England - M. Bağdatli; İlknur Uçak; Rowida Khalily (Innovations in Agriculture, 2023)
This study was conducted to determine the effects of climate change on agricultural production in England. In the study, some long-year average and some climate data were evaluated statistically on a monthly basis. In this study, temperature, precipitation, humidity, and rainy day data for a total of 31 years between 1991 and 2021 were used. Sunny day data were used as the average of 21 years of climate data between 1999 and 2019. As a result of this study, it was revealed that the long-year average of temperature (°C) was 10.77±4.9205, precipitation (mm) was 690.00±6.0076, humidity (%) 78.33±5.8827, rainy days : 94±0.5774 and sunny days (hour): 5.78±2.0564 in all months of the whole year from the research area in the North Sea to the east and south of England. According to studies, agricultural production is mostly affected by temperature, precipitation and humidity. The objective of this study is to check the impact of climate change on agricultural production in England.